A Bonaventurian rousing of the metaphysics of primary causality to counter New Materialism - Callum D. Scott (HTS Teologiese Studies/Theological Studies)
Bonaventure discerned the continuous presence of the problem of primary causality in contingent beings. From his perspective, full knowledge of the problem of primary causality emerges only when human reason is reduced to the first cause. In contrast, materialists do not consider primary causality because its empirically scientific epistemological method marginalises the idea of first cause (i.e., God). The zeitgeist of materialism and its entrenched reductionist ontology remains the core of physical and natural science in considering that all that has been is matter and holding that empiricist methods are the most reliable tools through which being can be investigated. These foundational premises are now reembraced in an in vogue ontology in the human and social sciences, New Materialism. In theology and religion, this paradigm has been applied too, despite the obvious perpendicularity in content and method of materialism when compared to metaphysical theorisations held as articles of Christian faith. Given that the human and social sciences are the natural home for expanding the conceptualisation of science, which might include faith, a case is developed that reductionist New Materialism influences against faith. Consequently, a twofold responsive model to New Materialism is made through Bonaventurianism: (1) by critiquing the absoluteness of materialist empiricism and (2) by arguing that reductionist epistemology is unreflective of multimodal being.